Creation of the Pancasila Village Profile Website as an Effort to Digitalize Village Information and Promotion - Muhammad Zidan Rosyid; Ni Putu Kartika Elsi Putri; Muhammad Fajril Rifaldo; Mohammad Taufiqurrahman; Della Oktaviani; Salha Athira Lubis; Qurrotuain Mufidah; Gilman Nur Ramadani (Konsienti : Community Services Journal, 2026)
The limitations of conventional media in conveying village information are a challenge in the digital era, especially in terms of reach, speed of updates, and efficiency of information distribution. Utilizing internet-based technology through a village website is a strategic solution to increase transparency, service effectiveness, and ease of access to information for the public. This study aims to design and develop the Pancasila Village Profile Website, Natar District, South Lampung Regency, as an information medium and a digital-based public service support tool. The village website not only functions as a medium for publishing the profile and potential of the region, but also as a means of providing information related to geographical conditions, population, government, education, and village development programs. The methods used include the stages of identifying village information needs, system design, website development, and implementation and functional testing. The results of the activity indicate that the village profile website is able to increase information accessibility, support transparency of village government, and become a means of promoting village potential to the wider community. Thus, the creation of a village website is a relevant step in supporting digital transformation and the progress of Pancasila Village.